Effects of software programs stimulating regular breaks and exercises on work-related neck and upper-limb disorders - van den Heuvel, Swenneke G.; de Looze, Michiel P.; Hildebrandt, Vincent H.; Thé, Kiem H. (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'This study evaluated the effects on work-related neck and upper-limb disorders among computer workers stimulated (by a software program) to take regular breaks and perform physical exercises. Possible effects on sick leave and productivity were studied as well. ' ' METHODS ': 'A randomized controlled design was used with cluster randomization. Altogether 268 computer workers with complaints in the neck or an upper limb from 22 office locations were randomized into a control group, one intervention group stimulated to take extra breaks and one intervention group stimulated to perform exercises during the extra breaks during an 8-week period. Questionnaires were administered before and after the intervention, and questions were generated by the software during the intervention period. Computer usage was recorded online. ' ' RESULTS ': 'The data on self-reported recovery suggested a favorable effect; more subjects in the intervention groups than in the control group reported recovery (55% versus 34%) from their complaints and fewer reported deterioration (4% versus 20%). However, a comparison between the reported pre- and postintervention scores on the severity and frequency of the complaints showed no significant differences in the change among the three groups. No effects on sick leave were observed. The subjects in the intervention groups showed higher productivity. ' ' CONCLUSIONS ': 'The use of a software program stimulating workers to take regular breaks contributes to perceived recovery from neck or upper-limb complaints. There seems to be no additional effects from performing physical exercises during these breaks.
Keywords: computer work; effect; exercise; microbreak; productivity; randomized controlled trial; regular break; rest break; sick leave; software program; work-related neck disorder; work-related upper-limb disorder